Carbon metabolism and biogeography of candidate phylum “Candidatus Bipolaricaulota” in geothermal environments of Biga Peninsula, Turkey - Coskun, Ömer K.; Gomez-Saez, Gonzalo V.; Beren, Murat; Ozcan, Dogacan; Hosgormez, Hakan; Einsiedl, Florian; Orsi, William D. (Frontiers in Microbiology, 2023)
Terrestrial hydrothermal springs and aquifers are excellent sites to study microbial biogeography because of their high physicochemical heterogeneity across relatively limited geographic regions. In this study, we performed 16S rRNA gene sequencing and metagenomic analyses of the microbial diversity of eleven different geothermal aquifers and springs across the tectonically active Biga Peninsula (Turkey). Across geothermal settings ranging in temperature from 43-79 oC, one the most highly represented groups in both 16S rRNA gene and metagenomic datasets was affiliated with the uncultivated phylum ‘Candidatus Bipolaricaulota’ (former Ca. Acetothermia and OP1 division). The highest relative abundance of ‘Candidatus Bipolaricaulota’ was observed in a 68 oC geothermal brine sediment, where it dominated the microbial community representing 91% of all detectable 16S rRNA genes. Correlation analysis of ‘Candidatus Bipolaricaulota’ operational taxonomic units (OTUs) with physicochemical parameters indicated that salinity was the strongest environmental factor measured associated with the distribution of this novel group in geothermal fluids. Correspondingly, a detailed analysis of 23 metagenome assembled genomes (MAGs) revealed two distinct groups of ‘Candidatus Bipolaricaulota’ MAGs based on the differences in carbon metabolism, one group encoding the bacterial Wood-Ljungdahl pathway (WLP) for H2 dependent CO2 fixation is selected for at lower salinities, and a second heterotrophic clade that lacks the WLP and was selected for under hypersaline conditions. In conclusion, our results highlight that the biogeography of ‘Ca. Bipolaricaulota’ taxa is correlated strongly with salinity in hydrothermal ecosystems, which coincides with key differences in carbon acquisition strategies. The exceptionally high relative abundance of apparently heterotrophic representatives of this novel candidate Phylum in brine geothermal environments observed in this study may help to guide future enrichment experiments to obtain representatives in pure culture.